(3GSJNOeGJ GdEOGQI GdYGeI aj GdNOeI GdGLJeGYjI hGdHMhK GdJbhjejI (B/s - (3NGWQ, GMeO eUWais ((3GdGScfOQjI(B: s (3GdecJHI GdLGeYjI(B, s, 2001)
(3GdJYQja HG dGOGQI hGdeaGgje PGJ GdYdGbI GdGOGQjIeY GdebGQfI ddeDSSGJ GdGLJeGYjI Hjf GdGOGQI GdYGeI hGOGQI GdGYeGd ,GdefXeI aj GdGOGQI h hXGFagG h YedjGJgG,GdJZjQ aj HfGA hhXGFa GdeDSSGJ GdGLJeGYjI h Jbhje eTQhYGJ GdQYGjI GdGLJeGYjI eY GSGdjH hJbfjGJ GdJbhje(B.s
Keywords: (3GdGOGQI GdYGeIs; (3GdHMhKs; (3GdNOeGJ GdELJeGYjIs